ФУНКЦИОНИРОВАНИЕ СОЦИАЛЬНО-ЭКОЛОГИЧЕСКОГО ПРОСТРАНСТВА - Субботина (Subbotina Tatiana), Татьяна Васильевна (Географический вестник=Geographical bulletin, 2017)
В исследовании обосновывается необходимость выработки новой функциональной модели пространственной организации территории (территориальной социально-экологической системы) с учётом постиндустриальных тенденций, деконцентрации общественной жизни и повышения статуса и общественной значимости периферийных зон «поляризованного ландшафта». Проводится территориальный анализ антропогенной нагрузки Пермского края с выделением факторов, проблем и направлений оптимального функционирования. FUNCTIONING OF SOCIO-ECOLOGIC SPACE Contradiction between natural and social components of landscapes is a source of development of different territorial systems. Functional aspect is a general approach in identification of interactions between components of territorial social-ecological systems (TSES). This abstract is invoked to analyze A. Lösch’s theory of economic landscape, as the first theoretical abstract, which consists of basic positions of the theory of spatial economic equilibrium. It’s noted that this theory is a logical part of structure of new information society. Moreover, it results fundamental transformation of functions of central places as the sources of information and knowledge. Besides, significance of network structure which functions depend on human behavior and creativity. The emphasis lies on the conception of polarized biosphere of B.B. Rodoman, which using the results to minimize the anthropogenic influence on nature thanks’ for optimal organization territorial zones between two interactional and complementary poles – big city and wild nature. The author has pointed out the discordance of polarized (ideal) and real landscape, the role of linear-central structure in territorial organization of society. As a result it needs to overview position and role of some peripheral zones of polarized landscapes (TSES at different position of territorial hierarchy). Finally, the author has illustrated territorial analysis and estimation of anthropogenic load for territories ofPermregion, where factors of load, problems of pollution and approach to optimal functioning ofPermmunicipal formations are determined. After types of municipal formations with different “weight” of anthropogenic load are revealed; it’s recommended its functional zoning.